Development of a Validated Interferon Score Using NanoString Technology - Kim, Hanna (J Interferon Cytokine Res, 2018)
Chronic elevation of interferon (IFN)-response genes (IRG) in a subset of patients with systemic immune-dysregulatory diseases, including the Mendelian Type-I IFN-mediated autoinflammatory diseases and some autoimmune diseases suggest a causative role of excessive IFN signaling in the disease pathogenesis and as target for treatment. We developed a 28-IFN response gene scoring system to calculate either a standardized or geomean score by customizing a NanoString assay to quantify the expression of putative IRGs. The gene targets were selected in patients with the IFN-mediated disease chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE) and an adult patient with chronic hepatitis C who received the first dose of pegylated interferon alpha-2a. The putative target genes were validated in patients with STING-associated vasculopathy with onset in infancy (SAVI), a monogenic autoinflammatory disease caused by gain-of-function mutations in TMEM173 that encodes the viral sensor stimulator of IFN genes (STING), and had low expression in clinically active patients with the monogenic IL-1-mediated autoinflammatory disease, neonatal-onset multisystem inflammatory disease (NOMID) and in healthy controls. The score calculation on the NanoString assay is rapid and showed high reproducibility and low intra-, and interassay variability. The utility of this 28-gene IFN score may be explored in the diagnosis of patients with presumed interferonopathies and as a biomarker to assess disease activity, long-term outcome, and treatment responses.